2011
DOI: 10.1590/s0100-55022011000100002
|View full text |Cite
|
Sign up to set email alerts
|

Erro médico: a perspectiva de estudantes de medicina e direito

Abstract: RESUMO Nas últimas décadas, houve um crescimento das implicações em-Education, Medical.-Ethics, Medical.-Legislation, Medical.-Liability, Legal. ABSTRACT Recent decades have witnessed an increase in the societal implications of medical error, a subject in which Medicine and Law intertwine. This study focused on medical error from the perspective of medical students and law students, assessing their level of interest and information and the need to discuss the topic during undergraduate education and how it oc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
2
0
4

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 17 publications
0
2
0
4
Order By: Relevance
“…Tal resposta pode estar associada à prática do direito não estar ligada aos processos que envolvem a assistência direta ao paciente. Corroborando com essa afirmativa, um estudo realizado em Minas Gerais, com 185 estudantes de Medicina e 119 alunos de Direito do turno diurno demonstrou que 68,6% dos estudantes de direito e 78,5% de medicina negaram a aptidão dos profissionais de Direito para interpretarem o erro do ponto de vista técnico (30).…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Tal resposta pode estar associada à prática do direito não estar ligada aos processos que envolvem a assistência direta ao paciente. Corroborando com essa afirmativa, um estudo realizado em Minas Gerais, com 185 estudantes de Medicina e 119 alunos de Direito do turno diurno demonstrou que 68,6% dos estudantes de direito e 78,5% de medicina negaram a aptidão dos profissionais de Direito para interpretarem o erro do ponto de vista técnico (30).…”
Section: Discussionunclassified
“…Esse mesmo estudo mostra que os estudantes de direito possuem mais disciplinas voltadas para leis de proteção do paciente, abordadas nas disciplinas de Códigos Civil, Penal, de Defesa do Consumidor e de Ética Médica, do que para as leis de proteção dos profissionais de saúde, o que pode ter contribuído para o desenvolvimento de tal compreensão. Por isso, destaca-se a abordagem desde a formação de conteúdos que envolvam a segurança do paciente, de modo a gerar futuros profissionais sensibilizados com as questões que tangem a saúde (30).…”
Section: Discussionunclassified
“…In 1999, the United States created the Agency for Healthcare Research and Quality. In 2002, at the 55th World Assembly of the World Health Organization, a Global Alliance was formed for patients’ clinical safety (Chehuen Neto, Sirimarco, Visoná de Figueiredo, Barbosa & da Silveira, 2011 ). In France, also in 2002, the National Office for Compensation of Medical Accidents was created with the purpose of working for people with health problems, and for the quality of the health care system (Grange & Papilon, 2008 ).4 Brazil still lacks initiatives such as these, which prioritize better quality, more humanized care between doctors and patients, and support better care for victims of medical errors.…”
Section: Discussionmentioning
confidence: 99%
“…A Brazilian study showed that future physicians were concerned regarding discussions on the issue given that, although they were knowledgeable on the subject, discussions and clarification on ways of working with such issue in professional life are lacking. Moreover, there seems to be a certain social pressure on future and active physicians given the difficulty experienced by the professionals involved in revealing or discussing real cases (Chehuen Neto et al, 2011;Custódio, 2016a).…”
Section: Introductionmentioning
confidence: 99%